Increasing Disciplinary for Children Age 5-6 Years through Traffic Simulation Games - Ekapuspahati, Herdian; Nurwaniasih, Nurwaniasih (Universitas Negeri Semarang, 2015)
Discipline in traffic is all kinds of behavior of the street user both with vehicles and without ones on the street according to the law. The teaching of it should be started as soon as possible to a child in order to obtain traffic disciplinary when a person lives in a society. The application by learning through traffic simulation is one of the ways that can be used to grow traffic disciplinary to a child aged 5-6 years old. The problem formula in this research is what are types of games applied in the learning through traffic simulation to the disciplinary of preschool students? Furthermore are there any influences of the application of such learning through traffic simulation in preschool students disciplinary? The purpose of the research is to know types of traffic simulation games applied n students’ learning process and to know whether applying learning through traffic simulation games influences the disciplinary of preschool students. The approach used in this research is a quantitative study. The population is students aged 5-6 years old in TK Bhayangkari Kecamatan Gajahmungkur Semarang. The sample is 30 students of grade B of TK Kemala Bhayangkari 90 and 30 students of grade B of TK Kemala Bhayangkari 08. Types of games used in the learning through traffic simulation games are the basic rule of pedestrians, the basic rule of bikers, the introduction of traffic signs, information of how to use a helmet, and manners on vehicles. After treatment given to experiment group, it is found that there was an increase in children’s traffic disciplinary, the mean in experiment group was 103.87 and control group 72.87. the score gained by the experiment group showed a higher number than the control group with the difference of 31,0 and the counting score on post-test of 10.282 with sig (2tailed) 0,00<0,05 which means Hi is acceptable thus there was a significant influence on applying learning through traffic simulation games to increase child’s traffic disciplinary.How to citeEkapuspahati, H. & Nurwaniasih. (2015). Increasing Disciplinary for Children Age 5-6 Years through Traffic Simulation Games. Indonesian Journal of Early Childhood Education Studies, 4(2), 90-95. doi:10.15294/ijeces.v4i2.9462DOI 10.15294/ijeces.v4i2.9462